Analysis of Protein Profile and Functional Groups in Biofilms in the Hypersaline Environment - Ilham Misbakudin Al Zamzami; Yuni Kilawati; Raudatul Ibdiah; Andi Kurniawan (Postgraduate, University of Mataram, 2023)
Halophilic microorganisms include extremophiles that can live and develop in a hypersaline environment. Biofilm, as microecology, consists of a collection of microorganisms attached to a surface, forming an Extracellular Polymeric Substance (EPS) matrix. This study aims to analyze the protein profile and functional groups of biofilms that grow in hypersaline environments. The method used in this study is the SDS PAGE test to diagnose protein profiling and FTIR to analyze biofilm functional groups. The samples used to grow the biofilm came from salt ponds with different NaCl levels, namely 2%, 25%, and 40%. The results showed that each NaCl treatment had different functional groups in the biofilm samples. In the 2% NaCl treatment, there were peaks with solid intensity at the wavenumber 1100 cm-1, indicating the carboxylic acid functional group. In the 25% NaCl treatment, peaks with solid intensity at wavenumber 2250 cm-1 indicate the isocyanate functional group. In the 40% NaCl treatment, there were peaks with solid intensity at wavenumber 860 cm-1, indicating the alkene functional group. The protein analysis for each treatment shows the presence of pyruvate kinase protein in the biofilm with 2% NaCl. The 25% NaCl biofilm sample contained avidin protein, and the 40% NaCl biofilm sample contained tyrosine protein.